Marquis de Sade: a biography - Lever Maurice (Harper Collins Publishers, 1993)
The name Sade has become synonymous with cruelty. To some he was a monster and a criminal; to others, an apostle of freedom who dared to expose society's hypocrisy in sexual matters. This biography aims to describe the real Marquis de Sade.